Studies in vegetation and soil of coastal salt marshes in the disko area, West Greenland. - Vestergaard, Peter (Meddelelser om Grønland, 1978)
At seven localities along the coasts of Disko and Nugssuaq the vegetation and soil conditions of salt marshes have been analysed by means of gradient analyses. In a number of sample plots along transects, which represent the change in vegetation with increasing elevation, the species composition was quantified by frequency and cover determinations, soil samples were taken at depths of 0-5 and 5-15 cm, and the relative elevation was established as the height of the plot above the lower salt marsh limit in percentage of the vertical range of the salt marsh. The number of species pr. m• in each plot and the species similarity between the plots along each transect were calculated. The soil samples were analysed for actual water content, cation exchange capacity, organic matter, specific conductivity, pH, water-extractable and NH,Acextractable Ca, Mg, K and Na, water-extractable Cl, H2S04-extractable P and EDT A-extractable Cu, Pb, Zn and Ni. From these data a number of derived soil data were computed. From the soil data in total, mean and standard deviation for each soil factor within six classes of relative elevation, and correlation coefficients between the soil factors mutual and between the soil factors and relative elevation, were computed. The vegetation and soil conditions of each locality are described, and the general trends in the vegetation structure and edaphic conditions of the salt marshes in relation to the height above the lower salt marsh limit, which seems to correspond to the mean high water level, are pointed out. It is shown, that the salt marshes form ecoclines from lower to upper marsh limit, composed by vegetational and environmental gradients. The ecocline has been divided into a lower and an upper salt marsh, dominated by Puccinellia phryganodes and Carex glareosa respectively; the vegetational and environmental characteristics of these marsh parts are described.